The Volatility of Foreign Portfolio Investment and the Access to Finance of Small Listed Firms. Issue 3 (August 2014) - Knill, April; Lee, Bong Soo
Abstract This paper examines the impact of foreign portfolio investment (FPI) volatility on the access to capital of small listed firms. The volatility of FPI is significantly associated with decreased access to finance for small listed firms only in years when nations are considered less "creditworthy." Even in these times, however, the benefits of FPI are not completely depleted. These results underscore the significance of both a good financial system that minimizes capital flow volatility and national creditworthiness in inspiring confidence in foreign investors.